Komunistyczne represje wobec ks. Paula Sauera (1892-1946) w świetle dokumentów Instytutu Pamięci Narodowej we Wrocławiu = Communist repressions against priest Paul Sauer (1892-1946) in the light of documents of the Institute of National Remembrance in Wrocław - Krzyżanowski, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The resolutions of the peace conferences crowned thc time of the Second World War, were not without an influence on the territorial shape of the Polish country and also on individual fate of people of both Polish and German origin. One of the consequences of establishing new borders was mass relocation of the Polish population from the East and displacement of the German population from the Western territories.
Keywords: Sauer, Paul (1892-1946); Instytut Pamięci Narodowej - Komisja Ścigania Zbrodni przeciwko Narodowi Polskiemu; Ziemie Zachodnie i Północne; źródła archiwalne